THE ROLE OF PARENTS AND TEACHERS IN ADOLESCENT DEVELOPMENT: A CASE STUDY OF CONSTRAINTS TO EFFECTIVE DISCIPLINE AMONG HIGH SCHOOL STUDENTS IN AWKA, NIGERIA - NNOROM, STANLEY U.; UGOCHUKWU, AGOGBUA VICTOR; HIMEZIE, MBONU VICTORIA; ABUCHI, EZENWAGU STEPHEN (Innovare Journal of Education, 2021)
The study was designed to investigate the constraints to the effective discipline of secondary school students in Awka South Local Government Area of Anambra state. The survey design was adopted for the study. Five research questions guided the study. The population of the study comprised 1320 teachers. A simple random sampling technique was used to select 150 respondents for the study. The instrument for data collection was a structured questionnaire titled “Constraints to Effective Discipline of Secondary School Student Questionnaire (CEDSSSQ).” The instrument was face validated by three specialists, two from Educational Management and Policy and one from Educational Measurement and Evaluation, all in the Faculty of Education, Nnamdi Azikiwe University, Awka. The questionnaire was trail-tested using Pearson Product Moment Correlation and was used to determine the reliability coefficient of the instrument and this yielded a reliability coefficient (0.74). Data were analyzed using frequency means to answer the research questions. Based on the findings, it was revealed that discipline problems encountered in secondary schools include: Truancy, stealing, assault on school prefects, absenteeism, fighting, and examination malpractice, among others. It was recommended, among others, that in order to stem indiscipline, specific disciplinary actions should be meted out against undisciplined students to discourage others from being unruly.